Pilot Survey of Outdoor Radon and Thoron Levels in Bulgaria Using an Innovative DVD-Based Method - Pressyanov, Dobromir; Dimitrov, Dimitar (Atmosphere, 2024)
This study presents the results of a pilot survey utilizing an innovative DVD-based method to measure outdoor radon and thoron levels. Twenty-six discriminative radon/thoron detectors were deployed across four different territorial zones in Bulgaria. Positioned 1 m above the ground, these detectors were left in place for several months. Notably, the dataset reveals significant variability in measurements, even over short distances, with thoron exhibiting greater variability than radon. Radon levels ranged from 7 ± 1 to 34 ± 3 Bq m−3 (average: 21 Bq m−3), while thoron levels ranged from 13 ± 5 to 307 ± 54 Bq m−3 (average: 170 Bq m−3). A weak but statistically significant correlation (correlation coefficient: 0.559) was observed between radon and thoron levels, which improved significantly when averaged across the four zones. These findings underscore the importance of measuring both radon and thoron in outdoor surveys. High thoron levels can significantly bias radon measurements, particularly when radon concentrations are substantially lower than those of thoron. If further studies confirm the good correlation between area averages, the observed correlation between area-average values could be used to correct average radon levels in large areas (e.g., radon priority areas) for thoron interference when thoron data are missing from the analyzed radon dataset.